O intercâmbio eletrônico de documentos (EDI) e a administração da cadeia de suprimentos - Costa, André Lucirton (1999)
This dissertation deals with the relationship between an information technology, EDI, and an organizational function, supply management. It analyzes the consequences of EDI implementation by correlating them with supply policies. The results were measured based on objectives such as quality performance, flexibility, costs, confiability and velocity. A field survey collected data from companies associated to ANF AVEA, ABRAS and SINDIPEÇAS and showed a non-rejection of the assumption that there is a correlation between supply practices and an information technology, EDI.